Magic Knight Rayearth. Part one. Book one - Tanaka, Melissa; Blackman, Abigail (Kodansha USA Publishing, LLC, 2023)
"Three girls who couldn't be more different meet on a school trip to Tokyo Tower--and find themselves beamed into a parallel world called Cefiro, where the mysterious Pillar has recruited them to avert a calamity! With the help of a motley troop of rogues and wizards, they will unlock the power of three transforming giant dragons known as Rune Gods and rush to the Pillar's aid...but there's more going on at the heart of Cefiro than they know!"--